# Answer to Question #16697 in Trigonometry for Mark

Question #16697

cos(x)^(4)-sin(x)^(4)=2cos(x)^(2)-1

Expert's answer

cos(x)^(4)-sin(x)^(4)=(cos(x)^(2)-sin(x)^(2)

)*(cos(x)^(2)+sin(x)^(2))= =cos(x)^(2)-sin(x)^(2)=cos(x)^(2)-(1cos(x)^(2))=2cos(x)^(2)-1

we

use here cos(x)^2+sin(x)^2=1

)*(cos(x)^(2)+sin(x)^(2))= =cos(x)^(2)-sin(x)^(2)=cos(x)^(2)-(1cos(x)^(2))=2cos(x)^(2)-1

we

use here cos(x)^2+sin(x)^2=1

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment